Insights into the Self assembled Lipid-Polymer hybrid Nanoparticles as Drug Delivery system - A.K. Pathak, Chandan Singh Ahirwar, (International Journal of Scientific Research and Management (IJSRM), 2017)
The Use of polymeric nanoparticles and lipid carrier systems, including liposomes, solid lipid nanoparticles and nanostructured lipid carriers has limitations such as drug leakage and high water content of dispersions. Thus, lipid polymer hybrid nanoparticles have been explored by the researchers to provide a better effect using biomimetic characteristics of lipids and architectural advantage of polymeric core and finally producing a system which overcomes the limitations of both polymeric nanoparticles and lipid carrier systems. The system composed of  biodegradable polymeric core surrounded by layers of phospholipids, additional compounds and mixtures may also be added to the phospholipids in the amphiphilic coating as for example fatty acids, steroids (such as cholesterol), triglycerides, lipoproteins, glycolipids, vitamins, detergents, and surface active agents. They are generally prepared by mixing liposomes and Polymeric nanoparticles to form lipid–polymer complexes in which a lipid bilayer or lipid multilayers cover the surface of the polymeric core. The space between polymeric core and lipid layer is usually occupied by water or aqueous buffer. The obtained particle size of the final particles remained in the desirable range with narrow distribution. The lipid-polymer hybrid nanoparticle by design has the capacity to co-encapsulate both hydrophobic and lipophilic drugs. The metabolic pathway of lipids in the body has led to the site specific delivery of such system with the modification of the pharmacokinetics and biodistribution of active ingredients for increased efficacy. This hybrid structure provides an advantages of controllable particle size, surface functionality, high drug loading, entrapment of multiple therapeutic agents, tunable drug release profile, and good serum stability. This review focuses on current research trends on Lipid Polymer hybrid nanoparticles including methods of preparation and physicochemical characteristics.